Role Studies Eligibility Business in Effort Development Product Business - Safitri, Novita; Mathory, Eljihad Akbari Syukriah (Relasi : Jurnal Ekonomi, 2025)
Micro, Small Enterprises Small and Medium Enterprises (SMEs) are a crucial foundation for the Indonesian economy, contributing significantly to Gross Domestic Product and employment. The Textile and Textile Products (TPT) industry in Indonesia plays a significant role in national economic development. One of the creative industry players in Makassar, Unggul Taman, plans to expand its business products through business diversification into a distribution channel. To ensure success and minimize risk, a business feasibility study was conducted to analyze the feasibility of this diversification. This study used a qualitative method with a descriptive approach. Primary data were collected through interviews and direct observation of Unggul Taman's owners and customers, while secondary data were obtained from from the study document like report finance And reference related. Analysis carried out on five aspect main that is aspect market And marketing, aspect management, aspect technical and operations, financial aspects and legal aspects. The results of the study show that the distribution business has potential market Which big, especially in circles young, supported by location strategic and product innovation. All aspects analyzed include market aspects, management aspects, technical aspects, aspect finance And aspect law, assessed worthy For support development business. Analysis finance show Net value Present Value (NPV) positive, Internal Rate An Inventory of Return (IRR) above 10% and a Payback Period of 1.5 years indicate a viable investment. The primary recommendation is to continue implementing business diversification according to the established plan. In conclusion, Unggul Taman's product development is feasible based on an in-depth analysis of various aspects. This business feasibility study provides an overview of promising opportunities and profits, and is expected to deliver tangible benefits to the company.